Robotic-assisted laparoscopic adrenalectomy (RARLA): What advantages and disadvantages compared to retroperitoneal laparoscopic adrenalectomy (RLA)? - Li, Xuwen; Xiao, Song; Yu, Yue; Liu, Wei; Xi, Haibo; Wang, Gongxian; Zhou, Xiaochen (Frontiers in Endocrinology, 2023)
Objective: To explore the advantages and disadvantages of robot-assisted laparoscopic adrenalectomy compared with retroperitoneal laparoscopic adrenalectomy. Methods: A total of 101 patients with adrenal tumors who received retroperitoneal laparoscopic adrenalectomy (RLA) (n=75) or robot-assisted laparoscopic adrenalectomy (RARLA) (n=26) in our hospital from January 2021 to December 2021 were retrospectively collected. Patients’ demographics, tumor characteristics, and perioperative indicators were compared. Statistical analysis was performed using t-test for continuous variables and Pearson chi-square test or Fisher’s exact test for categorical variables. Results: We found that blood loss in the RARLA group was significantly less than that in the RLA group (66.9 ± 35.5 ml vs 91.5 ± 66.1 ml, p = 0.020). Gastrointestinal function recovery time in RARLA group was significantly less than that in RLA group (19.9 ± 6.9 hours vs 32.0 ± 9.0 hours, p < 0.001). However, the operation time, drainage tube placement time, post-operative hospital stay in the RARLA group were significantly longer compared with the RLA group (149.6 ± 53.4 mins vs 118.7 ± 41.2 mins, p = 0.003; 4.9 ± 2.0 days vs 3.6 ± 1.1 days, p = 0.004; 6.4 ± 1.8 days vs 4.6 ± 1.6 days, p < 0.001). The hospitalization expense in the RARLA group is significantly higher than that in the RLA group (59284 ± 8724 RMB¥ vs 39785 ± 10126 RMB¥, p < 0.001). We found that there was no significant difference in the incidence of postoperative complications between the two groups. However, the pathological types of the two groups were significantly different. Patients in the RLA group had a higher proportion of adrenocortical adenoma, while patients in the RARLA group had a higher proportion of pheochromocytoma. Conclusion: Compared with traditional laparoscopic adrenalectomy, robot-assisted laparoscopic adrenalectomy can significantly reduce intraoperative blood loss and accelerate postoperative gastrointestinal recovery. It is committed to studying how to reduce the hospitalization time and hospitalization cost of RARLA, which can make RARLA more widely used.